2017
DOI: 10.3390/md15030068
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic Natural Products from Marine Sponge-Derived Microorganisms

Abstract: A growing body of evidence indicates that marine sponge-derived microbes possess the potential ability to make prolific natural products with therapeutic effects. This review for the first time provides a comprehensive overview of new cytotoxic agents from these marine microbes over the last 62 years from 1955 to 2016, which are assorted into seven types: terpenes, alkaloids, peptides, aromatics, lactones, steroids, and miscellaneous compounds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
48
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(48 citation statements)
references
References 57 publications
0
48
0
Order By: Relevance
“…It is important to understand the distinction between species, as there is a growing interest in natural products and other biobased studies from tetillids (e.g. Cleary et al 2013, Mokhlesi et al 2017, Zhang et al 2017). We expect that the current study can provide a solid basis for subsequent species descriptions of Indo-Pacific species of the genera Cinachyrella and Paratetilla .…”
Section: Resultsmentioning
confidence: 99%
“…It is important to understand the distinction between species, as there is a growing interest in natural products and other biobased studies from tetillids (e.g. Cleary et al 2013, Mokhlesi et al 2017, Zhang et al 2017). We expect that the current study can provide a solid basis for subsequent species descriptions of Indo-Pacific species of the genera Cinachyrella and Paratetilla .…”
Section: Resultsmentioning
confidence: 99%
“…This review highlights but a few of the compounds produced by microbial symbionts that have potential as pharmaceuticals [8,73,95,96]. For example, we draw readers to the recent excellent review by Zhang et al which describes in detail over 107 cytotoxic agents which have been discovered from 1955 to 2016 that are metabolized by marine sponge-derived symbionts alone [95] (including terpenes, alkaloids, peptides, aromatics, lactones, and steroids, amongst others).…”
Section: Constraints and Future Prospectsmentioning
confidence: 99%
“…For example, we draw readers to the recent excellent review by Zhang et al which describes in detail over 107 cytotoxic agents which have been discovered from 1955 to 2016 that are metabolized by marine sponge-derived symbionts alone [95] (including terpenes, alkaloids, peptides, aromatics, lactones, and steroids, amongst others). Several other recent detailed reviews are also available which provide information on the many compounds discovered from marine invertebrates, including cytotoxic, anti-microbial, anti-protozoal, anti-leishmanial, anti-trypanosomal and anti-inflammatory compounds, compounds which may actually originate from the host-associated microbes and not the invertebrates themselves [8,19,20,48,[97][98][99][100][101][102][103][104][105][106].…”
Section: Constraints and Future Prospectsmentioning
confidence: 99%
“…Previous chemical investigation indicated that Aspergillus genus is one of rich producers of terpenes, alkaloids, peptides, aromatics with a broad spectrum of biological activities (Zhang et al, 2017). Therefore, natural products …”
Section: Discussionmentioning
confidence: 99%
“…These microbes have potential capability to produce bioactive secondary metabolites with a broad spectrum of application in the field of medicine and agriculture (Bhatnagar et al, 2010;Zhang et al, 2017). More interestingly, marine sponge-derived fungi accounted for the largest number (33%) of natural products and had the highest number of new compounds during the period from 2003 to 2012 (Pejin et al, 2013).…”
Section: Introductionmentioning
confidence: 99%